2021
DOI: 10.5296/ijhrs.v11i4s.19236
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Job Stress, Job Performance and Job Motivation among Police Officers at the Federal Territory Police Headquarters

Abstract: Job performance is an important aspect of employees which ensures the efficiency and effectiveness of an organization. Job performance is influenced by job stress, while job stress affects job motivation. Hence, this paper is intended to identify the relationship between these three variables among Royal Malaysia Police (PDRM) officers at the Federal Territory Police Headquarters. This is a quantitative study for which data has been collected from 341 police officers through a survey. Data was analyzed statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…It was noted that gender significantly influences the mental component of HRQoL, particularly affecting aspects like vitality, social functioning, and mental health. However, gender did not significantly impact the levels of PA, echoing national trends [32] and findings from the study of military police in Feira de Santana, Bahia, by Jesus and Jesus [30]. In line with our findings, Ahmada et al identified various factors influencing job performance among police personnel, highlighting the complex interplay of physical health and job efficacy [38].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It was noted that gender significantly influences the mental component of HRQoL, particularly affecting aspects like vitality, social functioning, and mental health. However, gender did not significantly impact the levels of PA, echoing national trends [32] and findings from the study of military police in Feira de Santana, Bahia, by Jesus and Jesus [30]. In line with our findings, Ahmada et al identified various factors influencing job performance among police personnel, highlighting the complex interplay of physical health and job efficacy [38].…”
Section: Discussionsupporting
confidence: 89%
“…This study, therefore, focuses on exploring the interplay between PA and quality of life and the implications these factors have on professional performance within a law enforcement context. Similarly, Arujunan et al (2021) observed a significant relationship between job stress, job performance, and motivation among police officers, suggesting that enhanced physical activity levels may play a key role in modulating these aspects [30].…”
Section: Discussionmentioning
confidence: 96%